Pewarna Tinta - Mardanis Safwan (Jurnal Kimia dan Kemasan, 1985)
According to most historians, writing ink was first prepared and used by the Chenese the Egyptians. These early inks were probably composed of carbonaceous materials, such as lamp black or soot mixed with animal glue or vegetable oil vehicles. Writing inks differ from printing inks in that the latter are generally applied to a substrate by means of a printing press. Printing inks as supplied to the graphic arts industry are used in much greater volume by far as compared to writing inks. Inks make used of inorganid pigment and dyes, most commonly in the form of pigments that is to say, rendered insoluble in one of a number of way. Inks can be made of any desired tint, for a variety of pigments and dyestuffs are at the manufacturers; and the discovery of the coaltar colours, the main credit for which is due to Perkin, has increased their resources almost indefinitely, for they are now able to match any ray of the solar spectrum.